On the Role of the Blood Vessel Endothelial Microvilli in the Blood Flow in Small Capillaries - Makarov, Vladimir (J Biophys, 2015)
Endothelial microvilli that protrude into the capillary lumen, although invisible in the optical microscopy, may play an important role in the blood flow control in the capillaries. Because of the plug effects, the width of the gap between the capillary wall and the blood cell is especially critical for the blood flow dynamics in capillaries, while microvilli located on the capillary wall can easily control the velocity of the blood flow. We report that microvilli in the capillaries of different vertebrate species have similar characteristics and density, suggesting similarities between the respective regulation mechanisms. A simplified physical model of the capillary effective diameter control by the microvilli is presented.